2021
DOI: 10.1370/afm.2713
|View full text |Cite
|
Sign up to set email alerts
|

Voice Assistants and Cancer Screening: A Comparison of Alexa, Siri, Google Assistant, and Cortana

Abstract: Despite increasing interest in how voice assistants like Siri or Alexa might improve health care delivery and information dissemination, there is limited research assessing the quality of health information provided by these technologies. Voice assistants present both opportunities and risks when facilitating searches for or answering health-related questions, especially now as fewer patients are seeing their physicians for preventive care due to the ongoing pandemic. In our study, we compared the 4 most widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…However, interactive voice response systems remain relatively unexplored. A previous study has evaluated the quality of health information dissemination on cancer screening provided by voice assistants, such as Siri, Alexa, and Cortana, but did not evaluate these devices’ ability to screen for cancer [ 18 ]. One study evaluated the quality of speech intelligibility of Amazon Alexa and Google Home by providing individuals with intellectual disabilities with smart speaker devices [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, interactive voice response systems remain relatively unexplored. A previous study has evaluated the quality of health information dissemination on cancer screening provided by voice assistants, such as Siri, Alexa, and Cortana, but did not evaluate these devices’ ability to screen for cancer [ 18 ]. One study evaluated the quality of speech intelligibility of Amazon Alexa and Google Home by providing individuals with intellectual disabilities with smart speaker devices [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted pitfalls associated with the use of VAs as sources of health information, which often offer counsel that is inaccurate or incongruous with official recommendations [ 6 - 14 ]. Our study adds to this body of work by examining the responses of VAs to questions about the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increasing use of VAs by individuals and health care institutions to obtain and provide health information [2,3], VAs represent a tool that could, in theory, support the dissemination of evidence-based vaccine information. However, the literature assessing the reliability of health information provided by VAs is limited, and recent studies have found VAs provide users with health information that are inaccurate or incongruous with official recommendations [6][7][8][9][10][11][12][13][14]. For example, a content analysis of Amazon Alexa's responses to common pregnancy questions during the pandemic revealed that the majority (52%) of Alexa's responses were not evidence based [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAs have been variously used and studied in health care for supporting behavioral health and healthy living [3,4]; health information seeking [5][6][7][8][9]; appointment, medication, symptom tracking and chronic condition management [10][11][12]; and facilitating COVID-19 screening and information sharing [13,14]. Mobile phone ownership enables and increases the potential applications, availability, and access to CAs in practice.…”
Section: Introductionmentioning
confidence: 99%